Sandwich Generation: Copy Paste Nilai Teori Agensi dalam Keluarga Akuntan - Dini Fatihatul Hidayah; Krisno Septyan (Jurnal Akademi Akuntansi, 2024)
Purpose: This study aims to reveal the family dynamics of "sandwich generation" accountants who apply the values of agency theory in the family environment. Methodology/approach: This research uses a qualitative description method, interviewing accountants in the "Sandwich Generation." Researchers also interviewed their parents as a form of source triangulation. Findings: The results show that the application of agency theory values transforms family relationships into transactional and materialistic, which often leads to stress and conflicts of interest. Practical and Theoretical contribution/Originality: Agency theory, which naturally resides in corporations, has now permeated all of life, including family life. Research Limitation: The informant focused on her role as a sandwich generation without realizing that there were good memories with her parents.